Integrating socio-demographic factors for equitable resilience in networked-urban infrastructure systems - Feiya Chen; Shauhrat S. Chopra (npj Urban Sustainability)
Abstract While resilience assessments have begun considering equity, many fail to account for the nuanced impacts of infrastructure disruptions on sub-populations. This study hypothesizes the necessity of considering equity factors and empowering policymakers in tailoring plans for sub-populations during ‘black swan’ events. Departing from the ‘one-size-fits-all’ risk analysis, it promotes a more inclusive resilience perspective. Using the Travel Characteristic Survey dataset, the study examines socio-demographic, temporal, and spatial factors affecting the Hong Kong metro system’s resilience. Younger and older cohorts showed higher preparedness and robustness against both disruptions and attacks, but lower recovery capabilities. By mitigating disparities in resilience impacts, this framework shifts from utilitarian principles to integrating deontological theory in resilience analysis, recognizing citizens’ intrinsic value, advocating for social justice, and promoting sustainability. It also guides stakeholders in identifying stations needing improvements to address diverse social needs more efficiently. Moreover, it integrates resilience-by-design and resilience-by-intervention approaches, enhancing individual systems and external emergency measures.